A Rare Case of Rhinosporidiosis in Popliteal Fossa - Dr. Ranu Gupta; Dr. Saishruti Iyer (Tropical Journal of Pathology and Microbiology, 2021)
We hereby present a rare case of rhinosporidiosis in the popliteal fossa. Rhinosporidiosis is a chronic granulomatous infection caused by the fungus-like organism Rhinosporidium seebrii most commonly in the nasal cavity, followed by ocular and cutaneous lesions. The following case is of a 45-year-old female who presented to the laboratory with a pedunculated mass which on histopathology revealed a typical sporangium with numerous endospores. The report provides an insight into the clinical suspicion that needs to be kept while handling such cases.